Increased efficacy of omalizumab in atopic dermatitis patients with wild‐type filaggrin status and higher serum levels of phosphatidylcholines. Issue 1 (10th October 2013) - Hotze, M.; Baurecht, H.; Rodríguez, E.; Chapman‐Rothe, N.; Ollert, M.; Fölster‐Holst, R.; Adamski, J.; Illig, T.; Ring, J.; Weidinger, S.
Abstract Omalizumab, a monoclonal antibody targeting IgE, is an established therapy for severe allergic asthma and has shown efficacy in chronic spontaneous urticaria. Small‐scale studies indicated some beneficial effect also in atopic dermatitis (AD). To evaluate the efficacy of omalizumab in AD and to identify markers associated with treatment response, we conducted a prospective 28‐week open‐label trial on 20 adults with moderate‐to‐severe AD. Our results confirm previous observations of a positive response in a subgroup of patients and suggest that responders are characterized by the absence of filaggrin mutations and altered lipid metabolite profiles with high levels of various glycerophospholipids.